Design of a Big Data-based Evaluation System for Teacher-Student Cooperation in College English Writing - Li, Jia; Zhang, Jinpeng (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: With the constant change in information technology, people have entered the era of big data, and the reforms brought about by the era of big data have profoundly affected people’s way of life and learning. English writing is one of the four basic skills for mastering English, and the skilful mastery of writing is an essential form of accurate expression in English. Different from the traditional teaching modes of "separate assessment of teaching" and "separate assessment of learning", "cooperative assessment between teachers and students" is a new type of assessment mode proposed by professors at the National University in recent years. This cooperative evaluation model advocates the combination of the teaching and evaluation processes and the evaluation and learning processes. In the cooperative evaluation model, evaluation is considered an extension of the teaching process, and the evaluation process itself is also a school process. The arrival of the significant data era also brings new opportunities and challenges for university English teacher-student cooperative evaluation. OBJECTIVES: We design a university English writing teacher-student cooperative evaluation system based on big data by combining big data with the teacher-student cooperative evaluation. METHODS: All college English writing classes in one university were selected as the background for ample data research, and with the help of theoretical knowledge and technology related to big data, a model was constructed to analyze the factors affecting the cooperative evaluation system of college English writing teachers and students. RESULTS: The university English writing teacher-student cooperation evaluation system is analyzed and summarized using big data. CONCLUSION: By using big data to analyze the evaluation of college English writing teacher-student cooperation, big data can better help teachers understand the weaknesses of students’ knowledge points and better help students improve their English proficiency.